ESTIMASI KEBUTUHAN AIR IRIGASI PADI (Oryza sativa L.) DI DESA KOTO PERAMBAHAN KECAMATAN KAMPAR TIMUR BERDASARKAN MODEL SOFTWARE CROPWAT 8.0 - DEWI SAGITA; OKSANA OKSANA; TIARA SEPTIROSYA (Jurnal Agroteknologi, 2020)
Water availability is one of important factor to assure that a field could support increassing rice production value. These descriptive quantitative research aimed to get schedule and amount for irrigation water requirement based on climatic data, soil and crop. Data collected for these research were temperature, humidity, sunshine hours, wind speed, rainfall, plant morphology, altitude and latitude. The research was conducted on July until August 2019. Soil samples was carried out from field area in Koto Perambahan village, East Kampar sub district using purposive sampling method. Data was processed by Cropwat 8.0 software to get amount water requirement for replace the water losss caused of evapotranspiration. Based on weather condition, the field is suitable to plant rice in two season. Irrigation water requirement was writed in decade form, it means for ten days. First planting season occurred on March and irrigation water requirement was 180,6 mm/dec. Second planting season should be done on October with irrigation water requirement was 167,2 mm/dec. The highest irrigation water requirement was estimated on nursery stage, exactly in formation of rice tillers with approximately values 98 mm/dec.